Navigating artificial intelligence adoption in hospitality and tourism: managerial insights, workforce transformation, and a future research agenda - Shin, Hakseung; Ryu, Jiyoon; Jo, Yujeong (International journal of hospitality management, 2025)
As artificial intelligence (AI) and automation technologies continue to advance, hospitality businesses must embrace these innovations to remain competitive. While previous research has primarily focused on employee perspectives regarding issues such as retention and service quality, this study takes a managerial viewpoint to explore the factors influencing AI adoption, the managerial outcomes, and the evolving skill sets needed for frontline employees in the era of AI and automation. Through in-depth qualitative interviews with twenty-two accommodation managers and directors, recurring themes were identified, analyzed, and presented using thematic analysis. This approach revealed both facilitating and inhibiting factors in the adoption of AI technologies and provided insights into the consequences of such adoption. Moreover, the study proposes five essential skills necessary for frontline hospitality employees as AI becomes more prevalent. Building on these findings, the research presents a managerial framework and outlines a set of practical considerations and academic research questions to guide future investigations. •AI adoption, consequences, and hospitality employee skills were investigated.•Facilitating and inhibiting factors in the adoption of AI technologies were identified.•Managerial consequences of AI and automation technology adoption were examined.•The five essential skills necessary for frontline hospitality employees were identified.•Practical issues and academic research inquiries about hospitality AI adoption were proposed.